Flexible Power Regulation of Grid-Connected Inverters for PV Systems Using Model Predictive Direct Power Control - R S Ravi Sankar; S.V. Jayaram Kumar; K. K. Deepika (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper presents a Model Predictive Direct Power Control (MPDPC) strategy for a grid-connected inverter used in a photovoltaic system, as found in many distributed generating installations. The controller uses a system model to predict the system behavior at each sampling instant. Using a cost function, the voltage vector with least power ripple is generated. The resultant voltage vector is applied during the next sampling period which gives flexible power regulation. The effectiveness of the proposed MPDPC strategy is verified using MATLAB/ SIMULINK.